Alga Parasit Cephaleuros di Lingkungan Kampus Fakultas Biologi Universitas Gadjah Mada Yogyakarta - Muhammad Rizky; Airlangga Wibisono; Rifat Rizki Adi Nugroho; Della Putri Syalom; Japareng Lulang; Ludmilla Untari (Berkala Ilmiah Biologi, 2023)
Cephaleuros belongs to the family Trentepohliaceae, order Trentepholiales, and division Chlorophyta, and acts as a parasite on higher plants. The presence of this alga is characterized by the appearance of spots on the surface of the leaf epidermis and generally does not cause serious problems. However, in certain cases, this algal infection can cause serious problems to the leaves, fruits and stems of plants, especially in humid environments. This research objective is to identify the species of Cephaleuros in the campus of the Faculty of Biology, Gadjah Mada University, Yogyakarta. In this research, sampling was conducted using a purposive random sampling method. The samples were then identified based on macroscopic and microscopic characteristics. Two species of Cephaleuros, i.e. C. virescens and C. parasiticus, were identified as infesting several plants on the Faculty of Biology UGM campus. Each species is described and illustrated in the following article.